Pituitary follicle-stimulating hormone (FSH) induces CREM gene expression in Sertoli cells: involvement in long-term desensitization of the FSH receptor. - Monaco, L (1995)
Transcription factor CREM (cAMP-responsive element modulator) plays a pivotal role in the nuclear response to cAMP in neuroendocrine cells. We have previously shown that follicle-stimulating hormone (FSH) directs CREM expression in male germ cells. The physiological importance of FSH in Sertoli cell function prompted us to analyze its effect on CREM expression in these cells. We observed a dramatic and specific increase in the CREM isoform ICER (inducible cAMP early repressor) expression, with a peak 4 h after FSH treatment of primary Sertoli cells. Interestingly, induced levels of ICER protein persist for a considerably longer time. Induction of the repressor ICER accompanies early down-regulation of the FSH receptor transcript, which leads to long-term desensitization. Here we show that ICER represses FSH receptor expression by binding to a CRE-like sequence in the regulatory region of the gene. Our results confirm the crucial role played by CREM in hormonal control and suggest its role in the long-term desensitization phenomenon of peptide membrane receptors.